Peran Ambideksteritas Dinamis Dalam Efektivitas Pimpinan dan Dukungan Organisasi terhadap Pemecahan Masalah di Home Industri Bapak Sukir Desa Wedoro - Cakra WIbawa Khoiril Fadli; Didik Subiyanto; Jajuk Herawati (LPPM Institut Nasional Laa Roiba Bogor, 2024)
This study aims to determine the role of dynamic ambidexterity in the effectiveness of leadership and organizational support for problem solving in the home industry of Mr. Sukir Wedoro Village. This research method uses quantitative methods. The population in the study was about 40 employees located in Wedoro, East Java. In this study, using primary data by distributing questionnaires to each employee in the home industry. For data testing carried out using validity tests, reliability tests, respondent characteristics, normality tests, multicholinearity tests, heterochedasticity tests, linear regression analysis, hypothesis test (Partial Test, Simultaneous Test), and coefficient of determination. The data were processed using multiple linear regression analysis after testing for validity and reliability. (1) Leadership Effectiveness has no positive and significant effect on Problem Solving, (2) Dynamic Ambidexterity has a positive and significant effect on Problem Solving, (3) Organizational Support has a positive and significant effect on Problem Solving. This research contributes to understanding the Role of Dynamic Ambidexterity In Leadership Effectiveness And Organizational Support Towards Problem Solving. Based on the results of the analysis, not all variables have a positive and significant effect except for the Leadership Effectiveness variable does not have a positive and significant effect on Problem Solving. In addition to the Leadership Effectiveness variable, other variables such as the Dynamic Ambidexterity variable and the Organizational Support variable have a positive and significant effect. This research was only conducted in Mr. Sukir's industrial home in Wedoro village. Therefore, the collected data has a low normal level value. Keywords: Leadership Effectiveness, Dynamic Ambidexterity, Organizational Support, and Problem Solving.